Does fertiliser subsidy increase maize productivity in Burkina Faso?. Issue 3 (2nd April 2020) - Coulibaly, Adeline Doubahan; Savadogo, Kimseyinga
ABSTRACT: This article analyses the impact of Burkina Faso's fertiliser subsidy programme on the technical efficiency of maize producers using data on 710 maize producer households in Burkina Faso. According to stochastic frontier analysis estimation, the average level of the technical efficiency of the maize producers is 0.763. Using an interval regression model with endogenous treatment, the results revealed that households purchasing fertiliser from the market were more productive than the beneficiaries of the programme by 0.112 units. The results also showed that access to improved seed and membership of farmer-based organisations are factors increasing the probability of participating in a fertiliser programme.